Relationship between performance of different duration in racewalkers and runners - La Torre, A.; Biglietto, F.; Desalvo, F.; Bosio, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction It is commonly accepted that the time to complete long endurance events such as marathon is strongly related to the time to complete shorter endurance competitions like half-marathon and 10 km (Noakes, 1990). Based on these correlations, Noakes et al. (1990) suggested that the physiological factors to be successful in endurance events of 10-90 km could be the same. To date, the relationships between performance of different duration were not investigated and established in race-walking. These endurance events, despite the long duration, are different from running due to the complex technical ability required to "walk" at speed higher than 15 km/h. For this reason, the analysis of the relationship between 10 km, 20 km and 50 km is necessary as it can supply useful information from both a practical and physiological point of view. In addition, if these relationships exists, it is also interesting evaluate if it is possible to estimate change in performance during long endurance events from the change in performance during shorter competitions. Methods Using the IAAF database (www.iaaf.org), the Italian Track&Field Federation database (www.fidal.it) and the data of the ATFS (Association of Track and Field Statisticians, "Athletics 1991 - 2001" edited by Peter Matthews), race times of international level runners and race walkers from 1990 to 2002 were collected. From all the data at disposal, only race time of the runners who competed in the same competitive season both in 10 km, halfmarathon and marathon, and racewalkers who competed both in 10 km, 20 km and 50 km were selected. To verify the relationships between change in 10 km and change in race time of longer duration events, the data of endurance athletes who competed in all the events at least in two different competitive season were selected. Pearson`s product moment correlation was used to verify the relationship between race time of different duration. Significance was set at P<0.05. Results Correlations between performance of different duration were verified in 47 racewalkers and 37 runners (table 1 and 2), while associations between changes in 10 km time and marathon, and between 10 km time and half-marathon were determined on 17 and 19 runners, respectively. Relationships between changes in 10 km and 20 km time and between changes in 10 km and 50 km time were determined on 20 racewalkers. No statistically significant correlations were found between changes. Discussion/Conclusion The results of this correlational study confirm the relationships between endurance performance of different durations, i.e. the strongest athletes in shorter events tend to be also the best in longer competitions, and viceversa. However, these correlations, despite significant and good, were not sufficiently high to support the use of the linear regression equation, as suggested by Noakes (1990), for the prediction of the performance time (at least in an homogeneous group of high level runners and race-walkers). This was confirmed by the absence of correlations between changes in performance time. Despite this, a relationship between the ability to run and "walk" faster both in short and in long duration endurance events was confirmed by our results. This link is further highlighted by the observation than the best middle distance runners, recently competing in longer competition, are able to compete with the best marathon specialist. The hypothesis suggested by Noakes (1988) that skeletal muscle limiting factors, more than oxygen uptake regulation, could be determinant of endurance performance should be investigated more in depth.